A transmission protocol based on network coding in manytoone delay tolerant networks. (2015) - Sheu, JangPing; Lee, ChihYin; Ma, Chuang
In delay tolerant networks (DTNs), the delay of packets is long due to the intermittent connections caused by the mobility of nodes. Epidemic routing protocol (ERP) can reduce the delay time and raise the packet delivery rate by replicating and spread copies of source packets in the networks, but it inevitably exhaust memory resources and network bandwidth. In this paper, we propose a network coding with limited buffer routing protocol based on two network models, single packet network model and multiple packets network model. When a buffer of a node is full, two packets in the buffer are chosen randomly and encoded linearly together into a packet to save buffer space and improve the performance in manytoone communications. Moreover, in the transmitting stage of our network coding routing protocol, we proposed two efficient approaches that can enhance the efficiency of information exchange and packets transmission in communications of delay tolerant networks.